Pengaruh Lingkungan Kerja, Kompensasi dan Beban Kerja Terhadap Kepuasan Kerja di BPBD Kabupaten Bandung - Rismayanti, Ayu; Supiyadi, Dedi; Fanji, Fanji Wijaya (Jurnal Ilmu Sosial, Manajemen, Akuntansi dan Bisnis, 2024)
It is important to ensure that the company's employees are satisfied with their jobs, as this will directly or indirectly impact their work productivity. If employees are not satisfied with their jobs, negative attitudes toward work will emerge, such as employees' lack of interest in their jobs, their desire to find other jobs that offer more rewards or search for new jobs, and other complaints. The driving force for this research was to find out how BPBD Bandung Regency's work environment, compensation, and workload affect employees' levels of job satisfaction. There were 82 participants in this survey of BPBD Bandung Regency workers. Questionnaires are sent to participants in the study as part of the quantitative methodology—data analysis procedures involving validity and reliability testing. A statistical study using various regression formulae, partial tests, simultaneous tests, and the coefficient of determination is used for both descriptive and verification purposes. According to the findings, in BPBD Bandung Regency, job satisfaction is significantly impacted by work environment, compensation, and workload, which does not demonstrate any significant influence. Job satisfaction at BPBD Bandung Regency is greatly impacted by work environment, compensation, and workload.